Why AI’s role in advancing sustainability is underestimated - BHATTACHARYA, Lipika (Institutional Knowledge at Singapore Management University, 2025)
AI has quietly, but powerfully, woven itself into the fabric of our everyday lives. Yet, AI's potential impact on creating a more sustainable world is undervalued. The author examined artificial intelligence's (AI) role in advancing sustainability. She outlined how AI can be applied in various domains such as agriculture, water management, industry, urban planning, and biodiversity conservation for transformative effects.